Kajian Struktur Visual Pada Pasca Produksi Film Eksperimental “Sweet Rahwana” - Sasongko, Hery (IMAJI, 2023)
Experimental Film “Sweet Ravana” is a film artwork that raises about human nature that is translated through puppet approach. To realize the character in accordance with one of the human traits that exist in the puppet characters namely Ravana. Where Ravana is a figure of evil and always thirsty for power. In a movie there are some messages to be conveyed by the author. The message to be conveyed apart from the narrative aspect also through the cinematic aspect. In the experimental film "Sweet Ravana" this message to be conveyed made through shot attraction. Two previously unrelated shots then after going through the alignment process then generate a new meaning. The series of compositions of shots on the film is then the visual structure. Sintagmatik and paradigmatik is a theory that can be used to study the visual structure that exist in the experimental film "Sweet Ravana" with the aim to know the structure of the visual on the process jukstaposisi types of shot selection and editing.